2014
DOI: 10.1038/nrneph.2013.275
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and amiloride-sensitive sodium channels in vascular and renal cells

Abstract: This review is focused on the expression and regulation of amiloride-sensitive sodium channels in the epithelial cells of the aldosterone-sensitive distal nephron (ENaC) and amiloride-sensitive sodium channel activity in vascular endothelial and smooth muscle cells. Guyton’s hypothesis stated that blood pressure control is critically dependent on vascular tone and fluid handling by the kidney. With the study of Mendelian forms of hypertension and their corresponding transgenic mouse models, the main components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 202 publications
(237 reference statements)
0
100
1
Order By: Relevance
“…In the retinal choroid vascular bed, the activity of the KCa2.3 K + channel is requisite for the vasodilatory effect of aldosterone . The epithelial sodium channel (ENaC) is also modulated by aldosterone via MR in the endothelium (Kusche-Vihrog et al, 2008;Warnock et al, 2014). Because endothelial ENaC contributes to the stiffening The Mineralocorticoid Receptor in Pathology of endothelial cell membranes (Jeggle et al, 2013) and to the activity of eNOS (Perez et al, 2009), aldosterone/ MR modulation of endothelial ENaC expression/ activity is an important issue .…”
Section: A Mineralocorticoid Receptor Is a Regulator Of Ion Channelsmentioning
confidence: 99%
“…In the retinal choroid vascular bed, the activity of the KCa2.3 K + channel is requisite for the vasodilatory effect of aldosterone . The epithelial sodium channel (ENaC) is also modulated by aldosterone via MR in the endothelium (Kusche-Vihrog et al, 2008;Warnock et al, 2014). Because endothelial ENaC contributes to the stiffening The Mineralocorticoid Receptor in Pathology of endothelial cell membranes (Jeggle et al, 2013) and to the activity of eNOS (Perez et al, 2009), aldosterone/ MR modulation of endothelial ENaC expression/ activity is an important issue .…”
Section: A Mineralocorticoid Receptor Is a Regulator Of Ion Channelsmentioning
confidence: 99%
“…8 The epithelial sodium channel is also expressed in vascular endothelium and has been termed endothelial sodium channel (EnNaC). 9 As in epithelia, synthesis and activation of EnNaC is regulated by the mineralocorticoid hormone aldosterone. 10 Specific EnNaC blockade completely prevents sodium-induced stiffening.…”
mentioning
confidence: 99%
“…Although this change in plasma sodium is quite small it still may have considerable impact on vascular function. It has been shown that such a small change in plasma sodium stiffens vascular endothelial cells leading to endothelial dysfunction [12,13,14]. The only other significant change was found in the acid-base status (pCO 2 ) of patients with high salt sensitivity indicating a mild metabolic acidosis, compensated by hyperventilation.…”
Section: Resultsmentioning
confidence: 83%
“…Most likely this is caused by a mechanical interaction between RBC and vessel wall due to insufficient repulsive forces between the erythrocytes and the endothelial cell surface [8]. In the early days of hemodialysis mechanical destruction of erythrocytes during frequent hemodialysis was thought to be a major cause for anemia observed in these patients [7,8,9,10,11,12,13,14,15,16,17,18]. Along with the technical improvement of the dialysis equipment the adverse (mechanical) influence of the dialysis process by itself on erythrocyte survival became less [19,20].…”
Section: Discussionmentioning
confidence: 99%